PENGARUH KONFLIK PERAN GANDA DAN STRES KERJA TERHADAP KINERJA PEGAWAI WANITA DENGAN KESEIMBANGAN KEHIDUPAN-KERJA (WORK-LIFE BALANCE) SEBAGAI VARIABEL MEDIASI PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAKARTA PUSAT - Yohannes Ferry; Citra, Vinda Nirmala; Winarti, CH Endah; Erasashanti, Annthasia Puji; Sadipung, Theresia Oktavia (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2025)
This study investigates the complex relationships between work-family conflict, workplace stress, and the performance of female employees, with work-life balance serving as a mediating variable. The research was conducted at the Regional Office of the Directorate General of Taxes in Central Jakarta, focusing on female employees who face unique challenges in balancing their professional and personal responsibilities. This research utilized a quantitative approach, employing Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine data from 88 female employees selected through the Slovin sampling method from a total population of 688 employees. The Conservation of Resources Theory and Spillover Theory provide a theoretical framework for understanding the impact of work-family conflict and job stress on employee performance through work-life balance mechanisms. Research indicates that work-family conflict and job stress negatively impact employee performance, whereas work-life balance somewhat moderate these relationships. The findings reveal that female professionals facing increased work-family conflict and workplace stress demonstrate reduced performance, whereas those achieving a better work-life balance exhibit improved performance outcomes despite facing similar challenges. This study contributes to organizational behavior literature by providing empirical evidence of the mediating role of work-life balance in the relationship between workplace stressors and performance outcomes for female employees in the public sector. The findings suggest that companies should implement comprehensive work-life balance policies and support systems to enhance female employee performance and overall organizational effectiveness